2021
DOI: 10.3389/fpsyg.2021.613871
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Challenge and Hindrance Stressors on Thriving at Work Double Mediation Based on Affect and Motivation

Abstract: Although the relationship between stressors and thriving at work has been established, the linkage between them is still in the early stages of theory development. This study proposed a two-path model, based on Lepine’s stressors-performance model, to analyze the effects of the stressors on the thriving at work. Two complementary mediating paths were proposed, i.e., affective strain (positive affect) and motivation (self-efficacy), which were explained using affective events theory and expectancy theory, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 84 publications
2
27
0
4
Order By: Relevance
“…In contrast, challenge stressors are those assessed as being potentially beneficial for personal growth and gain. Challenge stressors can trigger positive emotions and desired work outcomes ( Yang and Li, 2021 ). Depending on the hindrance–challenge framework, studies indeed found that hindrance stressors have a negative and challenge stressors a positive relationship with important occupational criteria ( Cavanaugh et al, 2000 ; Boswell et al, 2004 ; Lepine et al, 2005 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In contrast, challenge stressors are those assessed as being potentially beneficial for personal growth and gain. Challenge stressors can trigger positive emotions and desired work outcomes ( Yang and Li, 2021 ). Depending on the hindrance–challenge framework, studies indeed found that hindrance stressors have a negative and challenge stressors a positive relationship with important occupational criteria ( Cavanaugh et al, 2000 ; Boswell et al, 2004 ; Lepine et al, 2005 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Stressors can translate into positive or negative outcomes based on the extent to which the stressors promote or hinder potential gains, known as challenge and hindrance stressors (Cavanaugh et al, 2000; Folkman & Lazarus, 1985; Jiang et al, 2020). Challenge stressors comprise opportunities like workload, responsibility, and time pressure (Yang & Li, 2021; Zhang et al, 2016). For instance, time pressure is a challenging stressor rather than a hindrance stressor and is considered useful when the duration of time pressure is kept to a minimum and manageable (Baethge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the score is, the higher the sense of thriving at work of the participants. The Chinese version of the questionnaire has been shown to have good reliability and validity in the Chinese teacher and nurse populations 37 38…”
Section: Methodsmentioning
confidence: 99%